Specific environmental conditions during 2008 Olympic games. Adaptative responses of the Spanish sailing team - Vaz Pardal, C.; Ruiz Verdeja, C. (Archivos de medicina del deporte, 2008)
Introduction: During the past four years in Qingdao, the Olympic Sailing Venue for the 2008 Olympic Games, mean air temperature was around 30 degrees Celsius and relative humidity at around 90%. Due to these extreme environmental conditions sailors` performance could have suffered and there was a greater risk of heat stroke as a result of increased body temperature Methods: How did Spanish Sailing Team prepare to face these extreme conditions? 1. Thermoregulatory methods (to control thermal stress and to reduce core temperature): a. Accurate control of the core temperature core body temperature sensors through a radio telemetry sensor. b. Precooling with ice-vests (Cryo-vest®) prior to competition and between daily races. c. Hydration control using quantitative determination of specific biological parameters such as sodium, potassium, Bicarbonate, pH, haemoglobin and hematocrit, by means of a portable clinical analyzer (I-STAT). 2. Individual supervision of the quality and quantity of fluid intakes based on I-STAT results. 3. Daily body weight checks before and after racing. Results: The core temperature during racing never exceeded 39.6ºC in the case of any members of the Spanish Sailing Team (in contrast to the previous year during the Olympic test event where peaks of 40,7ºC were recorder). The average variation in the sailors` body weight was 0,9±0,3 kg prior to and after racing. We could therefore deduce that sailors suffered no significant dehydration despite hot and humid environmental conditions. Conclusions: During the Olympic Games of 2008 in Qingdao, the Spanish Sailing Team, made up of 16 sailors, was able to maintain thermal balance despite the adverse environmental conditions. 1. Primarily due to the sailors undergoing a good adaptation process to the hot and humid climate by means of the methods adopted. 2. Secondly, as the environmental conditions during the Olympic Games were not as severe as expected: a. Mean temperature 26,9ºC. b. Mean relative humidity 77,8%